AKTIVITAS ANTIOKSIDAN METABOLIT SEKUNDER BAKTERI ENDOFIT AKAR TANAMAN Moringa oleifera L (Kelor) - Zeta Kuntari; Sumpono Sumpono; Nurhamidah Nurhamidah (University of Bengkulu, 2017)
[ANTIOXIDANT ACTIVITY OF SECONDARY METABOLITE FROM ENDOFIT BACTERIA OF Moringa oleifera L (KELOR) ROOTS] The purpose of this research was aims to isolate and measure the ability of antioxidant activity from secondary metabolites produced by endophytic bacteria that grow in the live tissue root of Moringa oleifera L. (kelor). Endophytic bacteria were purified and cultured using a solid Murashige-skoog (MS) medium for 3 days at room temperature. Secondary metabolites were obtained by centrifugation process at a rate of 3000 rpm for 20 minutes. The bacterial fermentation process using Nutrient Broth (NB) medium for 72 hours with a shaker speed at 170 rpm . The suspension supernatant was extracted with a maceration method using 86% ethyl acetate, followed by vacuum rotary evaporator concentration at 40 ° C. The extract antioxidant activity test was performed using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method using a UV-Vis spectrophotometer at 517 nm wavelength and ascorbic acid as standard. The result of DPPH test showed that the antioxidant activity of ethyl acetate extract of endophytic bacterial from root of M. oleifera L root has IC50 value at 315, 396 ppm. Based on these results, it can be concluded that the secondary metabolite extract of endophytic bacterial from M. oleifera L root classified as weak antioxidant (IC50> 250 ppm).